Payment by results and social impact bonds : outcome-based payment systems in the UK and US - Albertson, Kevin, 1963-; Fox, Chris (Bristol, UK : Policy Press, 2018)
As public services budgets are cut, the 'Payment by Results' (or Pay for Success) model has become a popular choice in public sector commissioning. Social Impact Bonds are a variant of Payment by Results also promoted by proponents of social (or impact) investing. But how effective are these approaches? This short book asks whether the Payment by Results model is an efficient way to unlock new capital investment, help new providers to enter the 'market' and foster innovation, or whether the extension of 'neoliberal' thinking, complexity and the effects of managerialism undermine the effective delivery of social outcomes.
The evidence to date on outcome-based commissioningWhere next for outcome-based commissioning?; In summary; References; Index.
Includes bibliographical references.
Online resource; title from digital title page (viewed on November 14, 2018).
JSTOR
Keywords: Municipal services -- Contracting out -- Great Britain; Municipal services -- Contracting out -- United States; Services municipaux -- Impartition -- Grande-Bretagne.; Services municipaux -- Impartition -- États-Unis.; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Municipal services -- Contracting out; United States; Great Britain; Contrats à impact social -- Grande-Bretagne.; Contrats à impact social -- États-Unis.; Services publics -- Gestion -- Grande-Bretagne.; Services publics -- Gestion -- États-Unis.; Administration publique -- Productivité.; Bibliographies